Boat Ticket Booking Information System at Mahakam Ulu Wharf - Yulianti Yulianti; Reza Andrea; Suswanto Suswanto (TEPIAN, 2023)
The background of this research is the Mahakam Ulu pier which provides traditional ship transportation services, while the problem that often occurs to prospective passengers is being left behind by ships because most of the prospective passengers do not get information about the departure schedule of the ship that the prospective passenger wants to go to. Therefore the purpose of designing a website-based ship ticket booking information system application at the Mahakam Ulu pier is to make it easier to order tickets online and make it easier for prospective passengers to get information about ship departure schedules, find out information about boat ticket prices, and find out what facilities are available. Provided on board, and also to make it easier for admins to manage ticket data. The development of the system used in this study is the waterfall method, to implement this ship ticket booking information system, supporting components are needed so that it can work properly. This component uses the Laravel framework programming and MySQL database. Based on the results of the black box test and the respondent's questionnaire, the web-based ship ticket booking system has been running well and can be used by customers and also the Mahakam Ulu jetty admin.